2019
DOI: 10.15252/embr.201948211
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric cohesin state revealed by live‐cell single‐molecule spectroscopy

Abstract: The cohesin complex plays an important role in the maintenance of genome stability. Cohesin is composed of four core subunits and a set of regulatory subunits that interact with the core subunits. Less is known about cohesin dynamics in live cells and on the contribution of individual subunits to the overall complex. Understanding the tethering mechanism of cohesin is still a challenge, especially because the proposed mechanisms are still not conclusive. Models proposed to describe tethering depend on either t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…These results in cells parallel observations in Xenopus extracts, in which inhibition of STAG incorporation into cohesin complexes interferes with cohesin occupancy on chromatin [8]. It is also consistent with a recent report suggesting that a STAG subunit is necessary for a conformational change within the cohesin core ring, promoting its stable association with chromatin [32]. However, we do note that simultaneous depletion of STAG1 and STAG2 fails to disrupt the interaction between the core cohesin ring and CTCF, in contrast with previous findings indicating that STAG proteins are the principal interface between cohesin and CTCF [35,36].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results in cells parallel observations in Xenopus extracts, in which inhibition of STAG incorporation into cohesin complexes interferes with cohesin occupancy on chromatin [8]. It is also consistent with a recent report suggesting that a STAG subunit is necessary for a conformational change within the cohesin core ring, promoting its stable association with chromatin [32]. However, we do note that simultaneous depletion of STAG1 and STAG2 fails to disrupt the interaction between the core cohesin ring and CTCF, in contrast with previous findings indicating that STAG proteins are the principal interface between cohesin and CTCF [35,36].…”
Section: Discussionsupporting
confidence: 91%
“…Our results demonstrate that STAG1 and STAG2 display nearly identical distributions across the genome, despite not interacting together in a stable complex. Our finding that the STAG proteins do not physically interact corroborates similar coIP and microscopy results in mESCs and human colorectal cancer lines, and is consistent with a model where cohesin functions as a single ring, rather than as a pair of rings [8,23,25,27,32,41,42]. Several recent reports have found that STAG1 and STAG2 localize at many shared sites, but also localize to a subset of sites exclusively [23][24][25]27].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…2A) (Huang et al, 2005;Zhang et al, 2008). More recent structural and spectroscopic studies provide strong support that tethering involves a single copy of the cohesin complex with two distinct chromatinbinding sites (model 2) (Chapard et al, 2019;Liu et al, 2020;Xu and Yanagida, 2019). However, evidence pointing to cohesin dimerization (Eng et al, 2014(Eng et al, , 2015 needs to be reconciled with this model.…”
Section: The Dual Role Of Cohesin In Sister Chromatid Cohesion and Interphase Chromatin Organizationmentioning
confidence: 99%
“…The cohesin complex regulates embryonic development in plants and animals by pairing sister chromatids during cell division and by influencing transcription (Minina et al, 2017;Smith et al, 2014;Marsman et al, 2014;Tedeschi et al, 2013;Mouri et al, 2012;Kawauchi et al, 2009). During S phase, replicated sister chromatids are connected with one another by the monomeric ring-like cohesin complex, and this cohesion is necessary for biorientation and orderly segregation of chromosomes on the mitotic spindle (Peters and Nishiyama, 2012;Skibbens, 2008;Liu et al, 2019). Interestingly, deficiency of nipped-B-like (Nipbl), the product of which facilitates cohesin loading (Hirano, 2006), results in fin bud undergrowth and transcriptional misregulation in the mouse limb bud (Muto et al, 2014), as well as tibial deficiency that is a feature in common with human cohesinopathies (Pfeiffer and Correll, 1993) and murine Irx3/ 5 deletion (Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%